Sensitivity of momentum-distribution asymmetry on ionization potential and atomic structure for ionization by few-cycle fields with two carrier frequencies - D. Habibović; D. B. Milošević (Physical Review Research)
When the strong-field ionization of atoms is induced by an ultrashort pulse instead of a long pulse with a flat envelope, many symmetry properties of the photoelecton momentum distribution are broken. The induced asymmetry is measured using the asymmetry parameter which depends on the values of the driving-pulse parameters and the type of the target. We investigate the driving pulses with two carrier frequencies because in this case the dependence of the asymmetry on the characteristics of the target is more robust. Particular attention is devoted to the pulse which consists of two circularly polarized few-cycle waves and the pulse which has two linearly polarized components with mutually orthogonal polarizations. In the former case, we show that the asymmetry parameter is highly sensitive to the ionization potential and to the structure of the ground state. This is particularly the case for the photoelectron energy just above the value for which the contribution of the electrons which do not interact with the core after the ionization becomes negligible. We explain this sensitivity by investigating the dependence of the short-travel-time saddle-point solutions on the characteristics of the target. On the other hand, for the driving pulse with linearly polarized components, the dependence of the asymmetry parameter on the ionization potential is significant, while the dependence on the structure of the ground state is relatively small. In conclusion, we show that the characteristics of the target are imprinted in the asymmetry parameter and this signature is more pronounced for two-component pulses than for the linearly polarized driving pulse with one carrier frequency.